Twenty-year effect of sewage-sludge fertilization in a Mediterranean grassland: Impact on species composition, functional groups and interrelation with climate - Valerio, Mercedes; Ibáñez, Ricardo; Lepš, Jan; Götzenberger, Lars (Perspectives in plant ecology, evolution and systematics, 2025)
Mediterranean semi-natural grasslands are biodiversity hotspots threatened by increased frequency of drought events, soil erosion and desertification. Soil amendment with sewage sludge is considered a sustainable practice to increase soil fertility and avoid erosion, though detailed studies on its long-term effects on vegetation dynamics are still missing. Understanding how fertilization with sewage sludge affects Mediterranean semi-natural grasslands is of multifaceted interest, from perspectives of waste management, ecosystem conservation, and vegetation ecology. We analyzed the vegetation dynamics of a grazing-excluded, semi-natural Mediterranean grassland over 20 years in response to a single sludge fertilization event. We studied the persistence of the effects of fertilization, the long-term temporal trajectory of the community, the response of species with different functional traits and from different functional groups, and the influence of fertilization on the interannual vegetation response to temperature and precipitation. Our findings revealed significant alterations in community species composition lasting over two decades following fertilization. However, fertilization effects seemed to start decreasing in the last years. Fertilization favored annuals with higher Specific Leaf Area. Fertilization also influenced the interannual response of the community to autumn temperature, June and summer drought differently depending on the species functional group and traits; herbaceous perennials with higher Leaf Dry Matter Content and lower leaf area decreased with summer drought, while the influence of summer drought in annuals and woody perennials was reduced. Our work underscores the importance of long-term ecological dynamics to understand the temporal magnitude of fertilization impacts on the species composition and functioning of plant communities. [Display omitted] •A single fertilization event leads to 20 years of changes in species composition.•Fertilization favors annuals with higher Specific Leaf Area over perennials.•Fertilization modifies successional processes, mitigating shrub encroachment.•RDA based on interannual changes in abundance reveals different plant strategies.•Fertilization affects how annuals and perennials respond to drought differently.